Uptake and Depuration of Phenol by Rohu (Labeo rohita) during a Chronic Sublethal Bioassay - P.M., Sherief; J.R., Rajasekharan Nair; P.S., Mrithyunjayan (Fishery Technology, 2025)
Studies on the body residue levels in surivors of bioassay tests can provide valuable information on bioaccumulation and organism tolerance, while residue in survivors allowed to depurate in clear water could furnish data on detoxification and elimination of pollutants. Early juveniles of rohu (Labeo rohita) were exposed to five sublethal concentrations of phenol (0.1,0.5,2.0,5.0 and 10.0 mg I"1) and a control under a static-with 48 h replacement procedure with nominal concentrations for a period of 28 days. The phenol body residue concentration increased from 8.17 to 24.85 mg kg"' whereas the bioaccumulation factor decreased from 81.7 to 2.5 as the phenol concentration in water increased from 0.1 to 10.0 mg I"1. The 72 h percentage depuration of the accumulated body phenol residues ranged from 58.5 to 71.2% on exposure to clear water. The study reveals that phenol as a pollutant has a low bioaccumulation potency and a high rate of depuration in fishes.